PENGELOLAAN KEUANGAN SYARIAH SEJAK USIA DINI DI DESA BOJONGKUNCI - Mukhlishah; Safitri, Nurlita; Junaedi Ramadhan, Enjang; Amelia, Nina; Ramdiyati Ismi, Alfita (LPPAIK Universitas Muhammadiyah Bandung, 2023)
In this day and age, money is a very useful thing. Using money is an activity that everyone does, from children to adults. The use of money is different, some manage to use money well and some do not. All people need to know the importance of managing finances and financial management education must be learned from an early age. Because without good financial management, it will have an impact on the economic welfare of the community. To develop an attitude of responsibility, the introduction of good financial management must be applied when entering junior high school (SMP). This research uses the method of implementing seminars and sharing which is carried out in Bojong Kunci Village aims to provide an understanding of: Principles of Islamic Economics, Embedding Ethical Values in Managing Finance, Development of Social Awareness: Through the introduction of the concept of zakat (mandatory donation) and infaq (voluntary donation), Formation of an Entrepreneurial Mindset Avoidance of Haram Transactions, Learning to Manage Finance Wisely and Future Preparation, Understanding the Concept of Interest and Risk, Understanding the principles of Islamic finance from an early age, the younger generation can contribute to a more just, sustainable and ethical society.